Uprighting of impacted lower third molars using brass ligature wire - Moro Naohiro; Murakami Teruo; Tanaka Takemasa; Ohto Chie (Sciendo, 2002)
As the orthodontic stage at the time of the eruption of the third molar is usually the retention period, it is desirable for both the patient and the clinician that impacted or inclined third molars be uprighted without an appliance. Impacted lower third molars can be successfully uprighted using only brass ligature wire. This paper suggests that brass ligature-wire therapy can be used to upright impacted molars that show considerable inclination.